Quantification of soil nutrient balance and stock on smallholder farms at Agew Mariam watershed in northern Ethiopia. Issue 4 (April 2023) - Esubalew, Tilahun; Amare, Tadele; Molla, Eyayu
Abstract: Soil fertility has been declining in many parts of Ethiopia, moreover limits agricultural production, sustainability and food security. Nutrient balance is used to evaluate the state of soil fertility, rate of nutrient depletion, sustainability of land productivity, as well as to take the appropriate management decisions. This study was conducted to quantify soil nutrient balance and stocks on smallholder farms at Agew Mariam watershed, in northern Ethiopia in the 2020/21 season. The inflows-outflows of NPK into, and out of barley, tef, and wheat farms were determined through, field measurement, laboratory analysis and interviews. The nutrient balance in each crop was quantified by subtracting nutrient outputs from the inputs. The N partial balance of barley, tef and wheat was −66, −9.8, and −50.7 kg ha −1 yr −1 fields, respectively. The P balance was also −5.9, 0.9, and −2.6 kg ha −1 yr −1 for barley, tef, and wheat fields, respectively. The K balance was −12.3, −3.2, and −5.4 kg ha −1 yr −1 in barley, tef, and wheat fields, respectively. The analysis revealed that N, P, and K had negative values except for P in tef. The stock of N was 1295, 1510, and 1240 in barley, tef, and wheat kg ha −1 fields, respectively. The P stock was 63, 18.7, and 27.5 kg ha −1 in barley, tef, and wheat farms, respectively. Similarly, K stock was 1092.7, 1059.4, and 1090.6 kg ha −1 in barley, tef, and wheat cropping systems, respectively. Reversing the imbalance between inflows and outflows via adding organic and inorganic fertilizer is essential for barley, tef, and wheat cropping systems in the study area.